In Vivo Characterization of Cortical and White Matter Microstructural Pathology in Growth Hormone-Secreting Pituitary Adenoma - Yuan, Taoyang; Ying, Jianyou; Li, Chuzhong; Jin, Lu; Kang, Jie; Shi, Yuanyu; Gui, Songbai; Liu, Chunhui; Wang, Rui; Zuo, Zhentao; Zhang, Yazhuo (Frontiers in Oncology, 2021)
Background: The growth hormone (GH) and insulin-like-growth factor 1 (IGF-1) axis has long been recognized for its critical role in brain growth, development. This study was designed to investigate microstructural pathology in the cortex and white matter in growth hormone-secreting pituitary adenoma, which characterized by excessive secretion of GH and IGF-1. Methods: 29 patients with growth hormone-secreting pituitary adenoma (acromegaly) and 31 patients with non-functional pituitary adenoma as controls were recruited and assessed using neuropsychological test, surface-based morphometry, T1/T2-weighted myelin-sensitive magnetic resonance imaging, neurite orientation dispersion and density imaging, and diffusion tensor imaging. Results: Compared to controls, we found 1) acromegaly had significantly increased cortical thickness throughout the bilateral cortex (pFDR < 0.05). 2) T1/T2-weighted ratio in the cortex were decreased in the bilateral occipital cortex and pre/postcentral central gyri but increased in the bilateral fusiform, insular, and superior temporal gyri in acromegaly (pFDR < 0.05). 3) T1/T2-weighted ratio were decreased in most bundles, and only a few areas showed increases in acromegaly (pFDR < 0.05). 4) Neurite density index (NDI) was significantly lower throughout the cortex and bundles in acromegaly (pTFCE < 0.05). 5) lower fractional anisotropy (FA) and higher mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD) in extensive bundles in acromegaly (pTFCE < 0.05). 6) microstructural pathology in the cortex and white matter were associated with neuropsychological dysfunction in acromegaly. Conclusions: Our findings suggested that long-term persistent and excess serum GH/IGF-1 levels impair the microstructure in the cortex and white matter in acromegaly, which may be responsible for neuropsychological dysfunction.